2022
DOI: 10.3390/vetsci9090477
|View full text |Cite
|
Sign up to set email alerts
|

Pathological Findings in Gastrointestinal Neoplasms and Polyps in 860 Cats and a Pilot Study on miRNA Analyses

Abstract: Background: Gastrointestinal masses in cats are of clinical relevance, but pathological studies with larger case numbers are lacking. Biomarkers such as miRNA have not yet been investigated in feline intestinal neoplasms. Methods: A retrospective analysis of pathology reports included 860 feline gastrointestinal masses. Immunohistochemistry was performed on 91 lymphomas, 10 sarcomas and 7 mast cell tumours (MCT). Analyses of miRNA-20b and miRNA-192 were performed on 11 lymphomas, 5 carcinomas and 5 control tis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 75 publications
1
2
0
Order By: Relevance
“…We confirmed that ddPCR using TaqMan miRNA assays is a robust technique for quantifying miRNA in canine FFPE samples, as previously shown in human and feline samples [ 30 , 31 , 32 ]. However, the isolation and quantification of miRNAs from FFPE material instead of fresh tissue is debatable.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…We confirmed that ddPCR using TaqMan miRNA assays is a robust technique for quantifying miRNA in canine FFPE samples, as previously shown in human and feline samples [ 30 , 31 , 32 ]. However, the isolation and quantification of miRNAs from FFPE material instead of fresh tissue is debatable.…”
Section: Discussionsupporting
confidence: 88%
“…Second, we investigated the miRNA profile of normal tissue compared with the different inflammatory and neoplastic diseases. We expected the two probably oncogenic miRNAs (miR-18b and 20b) to be up-regulated, as it has been described in canine T-cell lymphomas [ 16 ] and single samples of feline carcinomas, as well as T- and B-cell lymphomas [ 32 ]. Surprisingly, we did not find any mis-regulation of miR-18b in the T-cell lymphomas of the small intestine, or even down-regulation of miR-20b in the T-cell lymphomas and cases of lymphoplasmacytic enteritis of the small intestine.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation